The feeling of fear among local government administration employees as a result of the introduction of e-administration - Marek Bugdol; Magdalena Pokrzywa (Administrative Sciences, 2020)
The implementation and smooth functioning of e-administration depends on many technical and organizational factors but also on psychosocial factors, including the sense of fear. In this paper, the authors treat fear as a subjective and perceptible sense of threat. They recognize that employees may express various concerns. Previous research has shown that employees may be afraid of losing their jobs as a result of implementing e-administration. The introduction of technology brings with it the threat of dehumanization. There are also numerous concerns that the development of modern technologies will not ensure adequate economic growth because it will be too slow. This paper discusses issues related to the fear of the changes taking place in the present, in particular those related to the introduction of modern technologies, as well as problems related to the possibility of reducing unethical behavior. The research has been carried out in local administration offices using a qualitative research procedure. The results of the research indicate the existence of relationships between the quality of e-administration and fears or threats experienced or perceived by employees. If e-administration does not simplify work and does not reduce employees' workload, the only fears are employees' fear of change and their inability to master new information technologies. The data obtained allow management practitioners to overcome barriers related to the implementation of e-administration.
Keywords: 350; barriers; e-administration; fear; technological anxiety